(untitled) - Gerschenkron, Alexander (Cambridge, 1962)
These 14 essays covering a wide range of subjects of great current interest reflect the continuous evolution of the author's thought from 1951 to 1961. Range and flexibility characterize Mr. Gerschenkron's dynamic approach to Europe's industrial history. Connecting evolution in individual countries with their degree of economic backwardness, he presents the industrialization of the continent as a "case of unity in diversity," thus offering a cogent alternative, supported by case studies, to the traditional view of industrialization as monotonous repetition of the same process from country to country. Brought together for the first time, these essays were originally published in specialized periodicals in the United States and abroad.
Keywords: Industries,Industries,Industries,Công nghiệp,Công nghiệp,Công nghiệp; Soviet Union,Italy,Bulgaria,Liên Xô,Nướ Ý,Bulgaria